CD147: an integral and potential molecule to abrogate hallmarks of cancer - Nyalali, Alphonce M. K.; Leonard, Angela U.; Xu, Yongxiang; Li, Huayu; Zhou, Junlin; Zhang, Xinrui; Rugambwa, Tibera K.; Shi, Xiaohan; Li, Feng (Frontiers in Oncology, 2023)
CD147, also known as EMMPRIN, basigin, and HAb18G, is a single-chain type I transmembrane protein, it is overexpressed in aggressive human cancers of CNS, head and neck, breasts, lungs, gastrointestinal, genitourinary, skin, hematological, and musculoskeletal. CD147 is integral to the diverse but complimentary hallmarks of cancers, it plays a pivotal role in cancerous proliferative signaling, growth propagation, cellular survival, replicative immortality, angiogenesis, metabolic reprogramming, immune evasion, and invasion and metastasis. The molecule also has regulatory functions in the cancer-enabling characteristics, including DNA damage response (DDR) and immune evasion. These neoplastic functions of CD147 are executed through numerous and overlapping molecular pathways: it transduces signals from upstream molecules or ligands such as cyclophilin A (CyPA), CD98, and S100A9; activates a repertoire of downstream molecules and pathways including matrix metalloproteinases (MMPs)-2,3,9, hypoxia-inducible factors (HIF)-1/2α, PI3K/Akt/mTOR/HIF-1α, and ATM/ATR/p53; and also functions as an indispensable chaperone or regulator to monocarboxylate, fatty acid, and amino acid transporters. Induced loss of functions to CD147 prevents and reverses acquisition of the hallmarks of cancers in neoplastic diseases; it also alleviates resistance to chemoradiotherapy exhibited by malignant tumors such as carcinomas of the breast, lung, pancreas, liver, gastric, colon, ovary, cervix, prostate, and urinary bladder, as well as glioblastoma and melanoma. Targeting CD147 antigen in chimeric and induced-chimeric antigen T cell or antibody therapies is safe and effective. Moreover, the incorporation of anti-CD147 monoclonal antibodies in chemoradiotherapy, oncolytic viral therapy, and oncolytic virus-based-gene therapies increases effectiveness and reduces on-and off-target toxicity. This study advocates the expedition and expansion of exploiting the evidence acquired from the experimental studies that modulate CD147 functions in hallmarks of cancer and cancer-enabling features, translating them into clinical practice to alleviate the emergency, propagation, and clinical and social consequences of cancer.